Origin and role of the cerebrospinal fluid bidirectional flow in the central canal - Thouvenin, Olivier; Keiser, Ludovic; Cantaut-Belarif, Yasmine; Carbo-Tano, Martin; Verweij, Frederik; Jurisch-Yaksi, Nathalie; Bardet, Pierre-Luc; van Niel, Guillaume; Gallaire, Francois; Wyart, Claire (eLife, 2020)
Circulation of the cerebrospinal fluid (CSF) contributes to body axis formation and brain development. Here, we investigated the unexplained origins of the CSF flow bidirectionality in the central canal of the spinal cord of 30 hpf zebrafish embryos and its impact on development. Experiments combined with modeling and simulations demonstrate that the CSF flow is generated locally by caudally-polarized motile cilia along the ventral wall of the central canal. The closed geometry of the canal imposes the average flow rate to be null, explaining the reported bidirectionality. We also demonstrate that at this early stage, motile cilia ensure the proper formation of the central canal. Furthermore, we demonstrate that the bidirectional flow accelerates the transport of particles in the CSF via a coupled convective-diffusive transport process. Our study demonstrates that cilia activity combined with muscle contractions sustain the long-range transport of extracellular lipidic particles, enabling embryonic growth.
Keywords: cerebrospinal fluid; fluid dynamics; cilia dynamics; long range transport; embryogenesis; central canal